2015
DOI: 10.5812/ijhrba.24388v2
|View full text |Cite
|
Sign up to set email alerts
|

Crosswise Model to Assess Sensitive Issues: A Study on Prevalence of Drug Abuse Among University Students of Iran

Abstract: Background:Precise assessment of the prevalence of illicit drug use, face various methodological challenges.Objectives:The current study aimed to investigate the prevalence of illicit drug use among students studying at Universities in Shahroud (Northeast of Iran) through crosswise method.Patients and Methods:Participants of this cross-sectional study were 1646 students at Universities in Shahroud. The data collection instrument was a questionnaire designed based on crosswise model (CM).Results:The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…Moreover, the direct and indirect prevalence estimates of any illicit drug use in the previous studies in Iran range between 19% and 30.1%. [48][49][50][51] Although those studies differ from IranMHS in terms of the study population and duration of outcome, they support the estimate of 27% better than 3% for prevalence of illicit drug use in Iranian general population.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the direct and indirect prevalence estimates of any illicit drug use in the previous studies in Iran range between 19% and 30.1%. [48][49][50][51] Although those studies differ from IranMHS in terms of the study population and duration of outcome, they support the estimate of 27% better than 3% for prevalence of illicit drug use in Iranian general population.…”
Section: Discussionmentioning
confidence: 86%
“…Then, in addition to DQ, we evaluated the programme implementation by the CMan indirect method for asking sensitive questions. It was used successfully in research surveys about highly personal or sensitive questions such as addiction (16) , sexual behaviour (25) , cheating and plagiarism (20) . A more-is-better hypothesis has been assumed in these studies, and results indicated that the CM method provides a higher prevalence for sensitive behaviour (15) .…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the newest indirect questioning methods (15) . It has been used successfully to estimate the prevalence of sensitive issues such as illicit drug use (16,17) , sexual behaviour (18) , use of anabolic steroids by bodybuilders (19) and researchers' misconduct (20) . However, to the best of our knowledge, this method has not been previously used in assessing the implementation of health programmes.…”
mentioning
confidence: 99%
“…[23] implemented CD to estimate the prevalence of illicit drug use among the students of Tehran University of Medical Sciences. [24] used this design to investigate illicit drug use prevalence among students studying at Universities in Shahroud (Northeast of Iran).…”
Section: Crosswise Designmentioning
confidence: 99%